2017
DOI: 10.1007/s10815-017-0895-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of DNA methylation in imprinting disorders: an updated review

Abstract: Genomic imprinting is a complex epigenetic process that contributes substantially to embryogenesis, reproduction, and gametogenesis. Only small fraction of genes within the whole genome undergoes imprinting. Imprinted genes are expressed in a monoallelic parent-of-origin-specific manner, which means that only one of the two inherited alleles is expressed either from the paternal or maternal side. Imprinted genes are typically arranged in clusters controlled by differentially methylated regions or imprinting co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(83 citation statements)
references
References 165 publications
1
82
0
Order By: Relevance
“…DNA methylation is one of the most extensively studied epigenetic modifications of genomic DNA. Numerous DNA methylation studies have demonstrated that DNA methylation is critical in many regulatory processes such as silencing of gene expression, cellular differentiation, transposon mobility, genome stability, and genomic imprinting (Bewick and Schmitz, 2017;Elhamamsy, 2017;Niederhuth and Schmitz, 2017;Yaish, 2017;Bartels et al, 2018;Bräutigam and Cronk, 2018;Zhang et al, 2018). Much effort has been paid to characterize variation of DNA methylation across different biological samples, developmental stages, and disease status (Zhang et al 2006b;Dinh et al, 2012;Breuil-Broyer et al, 2016;Hewezi et al, 2018;Xu et al, 2018), however, changes in DNA methylation patterns associated with CRISPR/Cas9-mediated genome editing have not been explored yet.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation is one of the most extensively studied epigenetic modifications of genomic DNA. Numerous DNA methylation studies have demonstrated that DNA methylation is critical in many regulatory processes such as silencing of gene expression, cellular differentiation, transposon mobility, genome stability, and genomic imprinting (Bewick and Schmitz, 2017;Elhamamsy, 2017;Niederhuth and Schmitz, 2017;Yaish, 2017;Bartels et al, 2018;Bräutigam and Cronk, 2018;Zhang et al, 2018). Much effort has been paid to characterize variation of DNA methylation across different biological samples, developmental stages, and disease status (Zhang et al 2006b;Dinh et al, 2012;Breuil-Broyer et al, 2016;Hewezi et al, 2018;Xu et al, 2018), however, changes in DNA methylation patterns associated with CRISPR/Cas9-mediated genome editing have not been explored yet.…”
Section: Discussionmentioning
confidence: 99%
“…The epigenetic changes can be inheritable or environmental in nature and refer to changes which are in themselves reversible in nature. The epigenetic effects may give rise to phenotypical differentiated cells and tissues within an organism [2] [3].…”
Section: A Basic Overviewmentioning
confidence: 99%
“…Thus, it is an epigenetic route of modulating gene expression. Imprinting is a hereditary influence that is either a maternal or paternal epigenetic altering factor which pertains to the modified gene expression [2] [3].…”
Section: A General Introduction On Imprintingmentioning
confidence: 99%
See 1 more Smart Citation
“…These genes include imprinted genes that display different types of DNA methylation depending on their parental origin, leading to parental-allele-specific gene expression during development. Genome imprinting plays a key role in maintaining normal embryogenesis (Elhamamsy, 2017). In cattle, genomic reprogramming has been shown to be associated with an increase in the expression of transposable elements (TEs), specifically from a subclass of these elements called retrotransposons (Bui et al, 2009).…”
Section: Introductionmentioning
confidence: 99%